2020 IEEE Real-Time Systems Symposium (RTSS) 2020
DOI: 10.1109/rtss49844.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Survey-based Study into Industry Practice in Real-time Systems

Abstract: This paper presents results and observations from a survey of 120 industry practitioners in the field of realtime embedded systems. The survey provides insights into the characteristics of the systems being developed today and identifies important trends for the future. The survey aims to inform both academics and practitioners, helping to avoid divergence between industry practice and fundamental academic research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…During the review process for the preliminary version of this survey (Akesson et al 2020b), it was suggested that the survey findings might be common knowledge among the real-time systems community. In the best selling book Factfulness, Rosling-Ronnlund et al (2018) note that when asked simple questions about global or aggregate information, experts typically systematically get the answers wrong; often so wrong that they can be outperformed by random guesswork.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…During the review process for the preliminary version of this survey (Akesson et al 2020b), it was suggested that the survey findings might be common knowledge among the real-time systems community. In the best selling book Factfulness, Rosling-Ronnlund et al (2018) note that when asked simple questions about global or aggregate information, experts typically systematically get the answers wrong; often so wrong that they can be outperformed by random guesswork.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…On top of that, our algorithms do not limit the number of nodes and modes used to specify the target systems. The decision to support only the aforementioned system configurations at this early stage goes in line with one of the latest surveys of industrial practices in the real-time domain (Akesson, 2020). To validate our results, we expect to use our framework to analyze a set of industry-focused use cases and synthetic use cases that could represent problems that are not yet present in real-world applications.…”
Section: Proposed Workmentioning
confidence: 81%
“…The survey published by Akesson et al (2020Akesson et al ( , 2021, shows that about 80% of industry practitioners developing real-time systems are using multi-core processors, about twice the number that are using single-cores. On a single-core processor, when a task executes without interruption or pre-emption it has exclusive access to the hardware resources that it needs.…”
Section: Introductionmentioning
confidence: 99%